Pembuatan Komik Perpustakaan sebagai Media Rekreasi untuk Siswa Sekolah Dasar Kelas Rendah di Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Savitri, Dina; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractMaking comics as a media campaign for elementary school students in the Office of Archives and Library of West Sumatra Province is an effort made to bring closer between librarians with libraries. And the importance of planting reading interest from light and simple reading material is the method used to read into a habit that is liked by students. The making of this research uses descriptive theory with observation, interviews and understanding literature studies. After the data collection was done, the next stage in making comics was (1) Making comic story scripts based on interviews and observations (2) Drawing and drawing comics using Photoshop CS3 and Paint Tool SAI applications (3) Presentation of comics to be used in activities promotion. The use of comics is done by distributing comics to child service activities for free, so that it can be used as a communication tool between users and libraries.Keyword: comic making, promotion of the library